Physical Process Controlling the Surface Bacterial Community Composition in the Ulleung Basin of East Sea - Kim, Hyo-Ryeon; Lim, Jae-Hyun; Kim, Ju-Hyoung; Thangaraj, Satheeswaran; Kim, Il-Nam (Frontiers in Marine Science, 2022)
Although environmental drivers are known to shape the abundance and distribution of bacterial communities in the East Sea, the effects of physical processes have not been directly studied. Here, we aimed to examine the influences of water mass mixing (summer) and eddy circulation (winter) on the surface bacterial communities of the Ulleung Basin (UB), East Sea, based on the metagenomic approach. Overall, 490,087 operational taxonomic units (OTUs) were identified from five stations, and prokaryotic abundance was dominant at all stations in both seasons. Among the prokaryotes, most OTUs were affiliated with Proteobacteria, Cyanobacteria, Flavobacteria, and Actinobacteria during summer and winter. Bacterial communities were found to differ with water masses (Changjiang, Tsushima, and North Korea surface water) and eddy circulation, and were strongly correlated with environmental variables, suggesting specific bacterial community responses with specific seasonal physicochemical parameters. Our investigation indicates that together with distance and environment, advection shapes the UB bacterial community composition, helping us better understand the physical cues related to biological composition in the East Sea. However, further studies are needed to ascertain the role of microbial functional genes along with the advection of oceanographic processes in the East Sea to better understand the regional biogeochemical processes.